2007
DOI: 10.1111/j.1744-9987.2007.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PMX‐DHP Treatment for Patients With Directly Induced Acute Respiratory Distress Syndrome

Abstract: Endotoxin-removal direct hemoperfusion column containing polymyxin B immobilized fibers (PMX-DHP) is an effective procedure for the treatment of sepsis-induced acute respiratory distress syndrome (ARDS). We investigated retrospectively the effects and appropriate timing of PMX-DHP induction for directly induced ARDS in 38 patients. PMX-DHP was carried out twice for two hours. Blood pressure, heart rate (HR) and PaO(2)/FIO(2) (PF) ratio, leukocytes, platelets, endotoxin, inflammatory cytokines and clusters of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…A recent multi-center randomized controlled trial confirmed that PMX-DHP is more effective than conventional therapy in patients with sepsis [2] and indicated that PMX-DHP might favorably affect endotoxin levels, arterial blood pressure, vasopressor requirement, the arterial oxygen tension (PaO 2 )/inspiratory oxygen fraction (FiO 2 ) ratio (P/F) and mortality. Studies have also found that PMX-DHP is helpful for patients with complicated acute lung injury (ALI)/acute respiratory distress syndrome (ARDS), which is pathologically characterized by diffuse alveolar damage (DAD) [3,4,5,6]. DAD is also evident in some patients with rapidly progressive interstitial pneumonia (IP).…”
Section: Introductionmentioning
confidence: 99%
“…A recent multi-center randomized controlled trial confirmed that PMX-DHP is more effective than conventional therapy in patients with sepsis [2] and indicated that PMX-DHP might favorably affect endotoxin levels, arterial blood pressure, vasopressor requirement, the arterial oxygen tension (PaO 2 )/inspiratory oxygen fraction (FiO 2 ) ratio (P/F) and mortality. Studies have also found that PMX-DHP is helpful for patients with complicated acute lung injury (ALI)/acute respiratory distress syndrome (ARDS), which is pathologically characterized by diffuse alveolar damage (DAD) [3,4,5,6]. DAD is also evident in some patients with rapidly progressive interstitial pneumonia (IP).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, PMX-DHP has been shown to be an efficacious therapy for acute lung injury/acute respiratory distress syndrome despite their etiology [13,14,15,16]. Interestingly, several recent studies have demonstrated the possibility that PMX-DHP is also useful for the treatment of AE-IP [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…(Fig. 3) (12) and other recent studies have also proved that PMX treatment improves the PaO2/ FiO2 ratio (13) and suppresses the function of activated monocytes in the peripheral blood of ARDS patients (14). Further accumulation of clinical data is warranted for the evaluation of PMX treatment.…”
Section: Diffuse Alveolar Hemorrhage (Dah) Syndrome Is Caused By Bleementioning
confidence: 69%